Morphological and molecular evidence support a new truffle, Tuber sinomacrosporum, in Macrosporum group - Wan, Shan-Ping; Liu, Wei; Cui, Meng-Jin; Wang, Rui; Wang, Yu-Yun; Liu, Mei-Ju; Wang, Rui-Xue; Yu, Cheng-Jin; Yu, Fu-Qiang (Phytotaxa, 2023)
A new Chinese truffle species, Tuber sinomacrosporum belongs to the Macrosporum group was illustrated and described, it is characterized by brownish-red ascoma, prosenchymatous peridium, dark brown gleba, 1(2) spored asci and large ellipsoid ascospores with 2–6 μm high reticulate-alveolate. Molecular analysis of the internal transcribed spacers (ITS) of the nuclear ribosomal DNA supports this species is distinct from the known species within the Macrosporum group. Phylogenetic relationships and morphological differences between this new species and its related species are discussed.